Celebrations of the Week of Regained Territories and the Weeks of Western Lands between 1946–1948 Based on Nationwide Press Articles - Niewiadomski, Igor (Vade Nobiscum, tom XX/2019: Studia z historii politycznej i wojskowej, 2019)
The work presents the process of the celebration the Week of the ‘Recovered Lands’ and the Weeks of the ‘Western Lands’ between 1946–1948. The main historical source of it are Polish communist press. The events connected to these Weeks took place, on the scale of the entire country, between 1946–1970 with a break between 1949–1957. The author present a modes state of research which has so far been created on this subject. After that he describes the genesis of the Weeks and their course between 1946–1948. Mostly analyzed is the propaganda dimension of these events. It is done on the basis of the main press titles edited in the People’s Poland. Next, the author concludes that the Week of Recovered Lands and the Weeks of the Western Lands were one of the most exposed events for the main Polish communist which were supposed to strengthen the awareness of belonging Polish ‘Recovered Lands’ and a revision of Polish borders after 1945.